Has the project BALTEX so far met its original objectives? - Raschke, E.; Meywerk, J.; Rockel, B. (Boreal Environment Research Publishing Board, 2024)
After more than six years of build-up and basic research, the Baltic Sea Experiment (BALTEX) undergoes a transition into its second phase, where major attention is paid to provide a long-term data set, covering at least two complete seasonal cycles. This new phase called BRIDGE, is part of a world-wide effort to study energy and water cycles and also related fluxes of carbon and other constituents over continental-scale regions. Some of the major findings obtained during the first phase of BALTEX are summarized in this paper.